Seasonal Vascular Tissue Formation in Four Boreal Tree Species With a Focus on Callose Deposition in the Phloem - Montwé, David; Hacke, Uwe; Schreiber, Stefan G.; Stanfield, Ryan C. (Frontiers in Forests and Global Change, 2019)
We studied the seasonal dynamics of xylem and phloem formation in four boreal tree species that differed in leaf phenology (evergreen versus winter-deciduous) and wood anatomy (angiosperms versus gymnosperms). We sampled branch cuttings of balsam poplar (Populus balsamifera), trembling aspen (Populus tremuloides), lodgepole pine (Pinus contorta) and Siberian larch (Larix siberica) in bi-weekly intervals from the beginning to the end of the growing season. Cross sections were stained with astra blue and safranin in order to assess the width of the current year’s phloem and to distinguish between the current year’s mature and enlarging/ wall-thickening xylem. After enzymatic clearance of cytoplasmic components, we used scanning electron microscopy to observe seasonal patterns of callose deposition in sieve plates of balsam poplar. The sieve plate pores were not blocked by callose in April (prior to the start of the growing season) and in July. In October, after the end of the growing season, we found only minor callose accumulation, and only in a subset of samples. In three of the four species studied here, phloem formation in spring began before the start of xylogenesis, but the lag was shorter than what was previously reported for temperate environments with longer growing seasons. New xylem cells were first produced in trembling aspen, followed by lodgepole pine, balsam poplar and Siberian larch. Most of the xylem was produced in June and July, and all cells were mature in early September. Phloem production was mostly completed by early August. Balsam poplar had the shortest growing season in terms of cambial activity and leaf presence, suggesting a risk avoidance strategy with regards to frost damage.